Theoretical basis of decision-making model formalizing in frame of professional activity’s estimation algorithm with help of information technology - Заріцький, О. В. (Problems of Informatization and Control, 2015)
Actual question of decision-making model formalizing with aim of future using them duringdeveloping intellectual information technology for professional activity’s estimation and analysis, using multidimensional classification methods of statistics analysis